2013
DOI: 10.3109/07420528.2013.821128
|View full text |Cite
|
Sign up to set email alerts
|

Morningness–eveningness and sleep patterns of adolescents attending school in two rotating shifts

Abstract: School system in which classes are scheduled 1 week in the morning and the other in the afternoon, and in which students rotate schedule every week, fosters sleep irregularity. In this study, we examined morningness-eveningness of adolescents who were involved in such schedule of school time and explored relationship between their circadian preferences and sleep characteristics. A large sample of 2287 students between the ages 11 and 18 years (52% girls) from 24 schools in Croatia was studied. The School Sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 65 publications
3
24
0
1
Order By: Relevance
“…Adolescents who attended classes in an afternoon shift slept an average of 9 hours and 23 minutes during the week, which is slightly higher than has been reported in countries where the school system has an afternoon shift such as Croatia [72], Brazil [67,73], Greece [74], and even in an earlier study in Mexico [53] which report an average weekday sleep duration of 8 to 8.30 hours. Thus adolescents who have the opportunity to attend classes in an afternoon shift have a substantial sleep duration that meets the recommended duration [6,[60][61][62][63][64][65][66][67][68][69][70], regardless of their chronotype.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Adolescents who attended classes in an afternoon shift slept an average of 9 hours and 23 minutes during the week, which is slightly higher than has been reported in countries where the school system has an afternoon shift such as Croatia [72], Brazil [67,73], Greece [74], and even in an earlier study in Mexico [53] which report an average weekday sleep duration of 8 to 8.30 hours. Thus adolescents who have the opportunity to attend classes in an afternoon shift have a substantial sleep duration that meets the recommended duration [6,[60][61][62][63][64][65][66][67][68][69][70], regardless of their chronotype.…”
Section: Discussionmentioning
confidence: 52%
“…This lack of sleep brings with it a number of sleep problems, such as insomnia, daytime sleepiness, and disrupted sleep patterns [36], with the consequence of unsuitable conditions for school learning [89]. In comparison, adolescents who attend classes it an afternoon shift have better sleeping conditions, regardless of whether they have an orientation to eveningness or morningness, as also shown by Koscec et al [72]. In Mexico, this afternoon school shift is permanently implemented, so this allows us to compare the morning and afternoon shifts.…”
Section: Discussionmentioning
confidence: 72%
“…Nonetheless, the difference in school start times points to at least one of the likely contributors to Australian adolescents obtaining more sleep than adolescents in the US. In addition, a study of Croatian adolescents provides additional evidence of the effect of school schedule on youth's sleep patterns (Košćec et al 2014). Due to a lack of school space to accommodate all students simultaneously, most schools in Croatia have students on alternating schedules whereby students attend classes in the morning for 1 week and then in the afternoon the next week.…”
Section: School Start Timementioning
confidence: 99%
“…Due to a lack of school space to accommodate all students simultaneously, most schools in Croatia have students on alternating schedules whereby students attend classes in the morning for 1 week and then in the afternoon the next week. Using this naturally-occurring two-shift schedule, Košćec et al (2014) found that all youth (regardless of chronotype) delayed their bedtimes and wake times when in the afternoon versus morning school schedule. However, youth with an evening chronotype (as opposed to a morning or intermediate chronotype) showed the greatest irregularity, obtaining almost 2 fewer hours of sleep per night when on the morning school schedule than the afternoon school schedule.…”
Section: School Start Timementioning
confidence: 99%
“…Although high school begins early in the morning compared to elementary school and this change toward earlier start times during adolescence is not universal (Koscec et al, 2014), this misalignment between biological (evening preference) and social (early school time) time is very common among adolescents, who tend to be much later chronotypes than other age groups (Roenneberg et al, 2004). This mismatch between internal and external rhythms has been considered as a risk factor for low academic performance and poor health (Wittmann et al, 2006), and despite the fact that the effects of sleep deprivation have been extensively studied, there are not many studies which consider the effects of interindividual variables such as morningnesseveningness.…”
Section: Introductionmentioning
confidence: 99%